2015
DOI: 10.1371/journal.pone.0136878
|View full text |Cite
|
Sign up to set email alerts
|

G2/M Cell Cycle Arrest and Tumor Selective Apoptosis of Acute Leukemia Cells by a Promising Benzophenone Thiosemicarbazone Compound

Abstract: Anti-mitotic therapies have been considered a hallmark in strategies against abnormally proliferating cells. Focusing on the extensively studied family of thiosemicarbazone (TSC) compounds, we have previously identified 4,4’-dimethoxybenzophenone thiosemicarbazone (T44Bf) as a promising pharmacological compound in a panel of human leukemia cell lines (HL60, U937, KG1a and Jurkat). Present findings indicate that T44Bf-mediated antiproliferative effects are associated with a reversible chronic mitotic arrest cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 80 publications
5
17
0
Order By: Relevance
“…Although AKCs expressed CD29, CD44, CD73, CD90, and CD105 markers [1,34], their expression was significantly reduced in the AKCs after exposure to hWJSC-CM suggesting that AKCs were losing their stemness properties but not in controls. AKCs exposed to hWJSC-CM appear to be inhibited via apoptosis as they were arrested at Sub-G1 and G2/M phases [33], which is the same focal point of cell arrest by other anti-leukemic agents [35]. Furthermore, we observed increased numbers of Annexin-V-positive cells in AKCs exposed to hWJSC-CM compared to controls.…”
Section: Discussionsupporting
confidence: 54%
“…Although AKCs expressed CD29, CD44, CD73, CD90, and CD105 markers [1,34], their expression was significantly reduced in the AKCs after exposure to hWJSC-CM suggesting that AKCs were losing their stemness properties but not in controls. AKCs exposed to hWJSC-CM appear to be inhibited via apoptosis as they were arrested at Sub-G1 and G2/M phases [33], which is the same focal point of cell arrest by other anti-leukemic agents [35]. Furthermore, we observed increased numbers of Annexin-V-positive cells in AKCs exposed to hWJSC-CM compared to controls.…”
Section: Discussionsupporting
confidence: 54%
“…Previously, many studies have demonstrated that thiosemicarbazone derivatives induced mitochondria‐mediated apoptosis in cancer cells (Britta et al., ; Cabrera et al., ; Pessoto et al., ). Moreover, Bcl‐2 family members, caspase‐3, and caspase‐9 are the most important signaling proteins in the mitochondria‐mediated apoptosis pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Upon entry to the S phase, cdk2 associates with cyclin A, which is a protein that is highly involved in the progression in the cell cycle as its level increases steadily until the late G2 phase (Cabrera et al, 2015;Otto & Sicinski, 2017). Meanwhile, the activation of cyclin B-cdc2 complex, also known as the maturation promoting factor (MPF), regulates the transition in the G2/M phase as the activity of the CDK cdc2 is also responsible for governing the entry into the mitosis stage (Baldi et al, 2011;Cabrera et al, 2015;Lu et al, 2005;Zhang et al, 2017) In addition, significant downregulation of cdc25c, which is considered as a mitosis inhibitor, was also elicited by LPLC treatment. Cdc25c is a phosphatase, which prompts the entry into the mitosis phase, thereby inhibiting the arrest at G2/M phase through activation of cdk1(cdc2)/cyclin B complex (Cho, Park et al, 2015;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%